Status quo effect and preferences uncertainty: a heteroscedastic extreme value (HEV) model - Bakti Hasan-Basri,; Nurul Huda Yahya,; Rusmani Musa, (Penerbit Universiti Kebangsaan Malaysia, 2013)
Analysts must include the status quo (SQ) option as one of the alternatives in the Choice Experiments (CE) technique to ensure the technique is consistent with the Hicksian welfare analysis. However, it comes at a price. Usually, respondents choose the option not because it provides the highest utility but to avoid making difficult decisions or to protest the attributes trade-off. One solution for investigating the effect of the SQ option is through the inclusion of the alternative specific constant (ASC) in an estimation model. However, the solution is not applicable for an estimation model that has no ASC. In the present study, the heteroscedastic extreme value (HEV) model is applied to investigate the affect of the SQ effect on preference uncertainty. By analysing respondents’ preferences relating to attributes at recreational parks, the results suggest that more uncertainty exists in the SQ option, while less uncertainty exists in the hypothetical alternatives.